Optimal placement of DSTATCOM using Artificial Bee Colony Algorithm - V.Tejaswini, Dr.D.Susitra (International Journal of Advanced Science and Technology, 2020)
Poor power quality problems are existed in distribution system because of more consumption of reactivepower by the AC loads. DSTATCOM belongs to the family of custom power devices, which controlreactive power flow effectively. Hence, a new swarm intelligent optimization i.e., Artificial bee colonyalgorithm (ABC) is implemented in this paper to identify the optimal location of DSTATCOM in radialdistribution system. Main inspiration for artificial bee colony algorithm is intelligent foraging behavior ofhoney bees. Proposed artificial bee colony algorithm (ABC) is determining the optimal placing & sizingof D-STATCOM by solving power quality model. The solution encoded for minimization of Power loss &voltage stability index. The proposed algorithm is compared with traditional methods like GA, PSO &GWO in terms of convergence analysis.